Design and experimental validation of novel 3D optical scanner with zoom lens unit. (13th September 2017) - Huang, Jyun-Cheng; Liu, Chien-Sheng; Chiang, Pei-Ju; Hsu, Wei-Yan; Liu, Jian-Liang; Huang, Bai-Hao; Lin, Shao-Ru
Abstract: Optical scanners play a key role in many three-dimensional (3D) printing and CAD/CAM applications. However, existing optical scanners are generally designed to provide either a wide scanning area or a high 3D reconstruction accuracy from a lens with a fixed focal length. In the former case, the scanning area is increased at the expense of the reconstruction accuracy, while in the latter case, the reconstruction performance is improved at the expense of a more limited scanning range. In other words, existing optical scanners compromise between the scanning area and the reconstruction accuracy. Accordingly, the present study proposes a new scanning system including a zoom-lens unit, which combines both a wide scanning area and a high 3D reconstruction accuracy. In the proposed approach, the object is scanned initially under a suitable low-magnification setting for the object size (setting 1), resulting in a wide scanning area but a poor reconstruction resolution in complicated regions of the object. The complicated regions of the object are then rescanned under a high-magnification setting (setting 2) in order to improve the accuracy of the original reconstruction results. Finally, the models reconstructed after each scanning pass are combined to obtain the final reconstructed 3D shape of the object. The feasibility of the proposed method is demonstrated experimentally using a laboratory-built prototype. It is shown that the scanner has a high reconstruction accuracy over a large scanning area. In other words, the proposed optical scanner has significant potential for 3D engineering applications.